(untitled) (Journal of Economic Research & Business Administration, 2018)
The article discusses the main approaches to the formation of financial statements in accordance with international financial reporting standards and the possibility of using these approaches in the preparation of financial statements of the company. The current system of accounting and reporting does not fully ensure the proper quality and reliability of the information generated in it, and also significantly limits the possibility of useful use of this information. Therefore, improving the quality of information generated in the financial statements and ensuring guaranteed access to it by interested users remains the main task of reforming accounting. The concept of development of accounting and reporting is aimed at improving the quality of information generated in financial accounting and reporting, and ensuring guaranteed access to it by interested users. A qualitative approach to an enterprise’s strategy should be based on the fact that quality is both the most effective means of meeting needs and a means of reducing costs. The first attribute of the quality of information provided in financial statements is that it is readily understandable by a user who has sufficient knowledge of business and economic activities, accounting and a willingness to study the information with due diligence.